A comprehensive study of food prices and food fraud in the European Union - Trajkovikj, Filip; Todorovska, Ana; Peshevski, Dimitar; Nakova, Lina; Trajanoska, Milena; Dobreva, Jovana; Stojanov, Riste; Trajanov, Dimitar (IEEE, 2023)
This research delves into the intricate dynamics of food pricing and fraud within European Union member countries. We analyze the complex interplay between food categories and countries, unraveling unique pricing trends and potential anomalies. By computing inflation-adjusted expected prices and sourcing real prices, we gain a deep understanding of inflation’s impact on actual food costs. Our multi-level analyses, network-based approaches, and cluster maps provide a global perspective, revealing international correlations in food pricing and fraud. The significance of our findings lies in setting the groundwork for understanding food fraud, informing strategies for fraud prevention, consumer protection, and, ultimately, food sustainability. Our work serves as a crucial resource for policymakers, economists, and consumers, emphasizing the importance of data-driven decision-making and transparency in the ever-evolving landscape of the European food market.
Keywords: food; food prices; food fraud; inflation; networks